Structural Bonus of Factor Productivity in China’s High-Tech Industry: A Cross-Sector, Cross-Province, and Cross-Ownership Study - Peigang, Liu; Rensel, Ann; Lee, Tenpao; Pei, Mao (Journal of Applied Business and Economics, 2018)
The evolution of Chinese high-tech industry labor force and capital structure is analyzed using a shiftshare technique. Contributions from cross-sector, cross-province and cross-ownership flows of factors to productivity growth were assessed. Cross-sector labor force flow produced “positive structural bonus”, cross-sector capital flow produced “negative structural bonus”, cross-province labor flow produced “negative structural bonus”, cross-province capital flow produced a “positive structural bonus”, crossownership labor and capital flow produced “positive structural bonus.” Implications are decrease intervention in operations, allow free factor movement among sectors, provinces, and ownership; improve capital market and improve labor market to channel skilled workers into the high-tech industry.